Metode Living Qur’an Sebagai Penanganan Masalah Dalam Lingkungan Masyarakat - Mahfud alizar Mahfud (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
The purpose of research on the living qur'an method as a problem handling in the community environment is to find a specific way in which the living qur'an method is effective in dealing with problems that occur in society. In this research, it uses a qualitative type with a literature study method. With data collection techniques, namely documentation such as; books, journals, magazines and more. The results of the research, that the researcher provided clarification on the existing problems about the qur'an living method as a handling of problems in the community environment, namely: First, the meaning of the Living Qur'an Method from a form of management here that a book of the Qur'an can live in the life of society which means that man does something according to the meaning contained in the Qur'an. It can be interpreted that we as Muslims should be able to learn more or worship the Qur'an and practice what we know in order to achieve broad knowledge. Second, the Application of the Living Qur'an Method in Community Life that from the management side, in the application of the living Qur'an method, it must have a living qur'an approach to reflect the community. So that these people can apply the meaning of the Qur'an in their lives. Third, the Function of the Living Qur'an Method towards Society lies from management here that a person will change by itself if he administers the Qur'an so as to make changes for oneself and the surrounding environment so as to create a harmonious environment between one another so as to create a peaceful environment. The Qur'an provides the right way so that people can walk their way, therefore humans are required to learn constantly to know broad knowledge so that humans continue to develop in terms of knowledge.